2023
DOI: 10.1038/s41598-023-31421-1
|View full text |Cite
|
Sign up to set email alerts
|

Lithium and brine geochemistry in the Qianjiang Formation of the Jianghan Basin, central China

Abstract: The Li-enriched oilfield brine is a very important lithium resource. It has gained much attention and become the target of active Li surveys with the growing global demand for Li. However, only little is known about their feature and nature. In the study, hydrochemical data from 155 oil wells tapping the Eocene to Lower Oligocene Qianjiang Formation of the Jianghan Basin, central China indicate that the brines are of the Na–Cl or Na–Ca–Cl type and are characterized by highly variable Li contents of 7.56 to 150… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Li et al [43] reported Li + concentrations ranging from 110 to 237 mg/L in the Nanyishan and Dafengshan oilfields in the Qaidam Basin, Tibetan Plateau. The recent findings of Yu et al [44] confirm variable Li + contents from 7.5 to 150 mg/L in the Qianjiang Formation in central China.…”
Section: Volume Current Usage and Composition Of Oilfield Brinesmentioning
confidence: 73%
See 1 more Smart Citation
“…Li et al [43] reported Li + concentrations ranging from 110 to 237 mg/L in the Nanyishan and Dafengshan oilfields in the Qaidam Basin, Tibetan Plateau. The recent findings of Yu et al [44] confirm variable Li + contents from 7.5 to 150 mg/L in the Qianjiang Formation in central China.…”
Section: Volume Current Usage and Composition Of Oilfield Brinesmentioning
confidence: 73%
“…Therefore, the concentration of lithium cannot be predicted on the basis of simplified analyses of basic ions and must be determined separately for each time. Yu et al [44] created a unique database containing hydrochemical data from 155 oil wells. The statistical analysis of this dataset confirms that lithium concentration has a weak relationship with the salinity and content of individual ions as shown in Figure 3a-d.…”
Section: Volume Current Usage and Composition Of Oilfield Brinesmentioning
confidence: 99%
“…Most of the samples meet or exceed the threshold for industrial grade, with some even reaching the lowest industrial grade.Li is a crucial element in the 21st century, serving as an energy source and lightweight alloy material. It is widely used in various industries such as atomic energy, aerospace, defense, metallurgy, electronics, glass ceramics, petroleum, chemicals, batteries, rubber, steel, machinery, and medicine(He, 2011;Yu et al,2023;Ding et al,2023;. In the study area, the Li + content in the brine ranged from 11.08 to 79.34mg/L, with an average of 35.16mg/L.…”
mentioning
confidence: 99%